Deep in a Dream : the Long Night of Chet Baker. - Gavin, James (Chicago Review Press, 2011)
From his emergence in the 1950s as an uncannily beautiful young Oklahoman who became the prince of "cool" jazz seemingly overnight to his violent, drug-related death in Amsterdam in 1988, Chet Baker lived a life that has become an American myth. Drawing on hundreds of interviews and previously untapped sources, this first major biography of one of the most romanticized icons in jazz gives a thrilling account of the trumpeter's dark journey. Author James Gavin delves deeply into Baker's tormented childhood, the origins of his melancholic trumpet playing, and even reveals the long-unsolved riddl.